Can drip irrigation technology be socially beneficial? Evidence from Southern India - Kumar, D.S.; Kuppannan, Palanisami (IWA Publishing, 2011)
Drip irrigation has received considerable attention from policy makers because of its significant contribution towards resource saving, enhanced agricultural productivity and environmental sustainability. This paper explores the potential benefits of drip irrigation adoption by addressing the social benefits and costs in Southern India. The study shows that adoption of drip irrigation technology has resulted in significant external and private benefits. The social benefit-cost ratio (SBCR) ranged from 4.33 to 5.19 at a 2% discount rate under different scenarios across regions. This confirms that a wide adoption of drip irrigation produces sufficient social benefits to justify the subsidization of drip irrigation. Water management policy should focus attention on the promotion of drip irrigation in regions where water and labour scarcity are critical.